Coq theorem proving: Simple fraction law in peano arithmetic - coq

I am learning coq and am trying to prove equalities in peano arithmetic.
I got stuck on a simple fraction law.
We know that (n + m) / 2 = n / 2 + m / 2 from primary school.
In peano arithmetic this does only hold if n and m are even (because then division produces correct results).
Compute (3 / 2) + (5 / 2). (*3*)
Compute (3 + 5) / 2. (*4*)
So we define:
Theorem fraction_addition: forall n m: nat ,
even n -> even m -> Nat.div2 n + Nat.div2 m = Nat.div2 (n + m).
From my understanding this is a correct and provable theorem.
I tried an inductive proof, e.g.
intros n m en em.
induction n.
- reflexivity.
- ???
Which gets me into the situation that
en = even (S n)
and IHn : even n -> Nat.div2 n + Nat.div2 m = Nat.div2 (n + m), so i don't find a way to apply the induction hypothesis.
After long research of the standard library and documentation, i don't find an answer.

You need to strengthen your induction hypothesis in cases like this.
One way of doing this is by proving an induction principle like this one:
From Coq Require Import Arith Even.
Lemma nat_ind2 (P : nat -> Prop) :
P 0 ->
P 1 ->
(forall n, P n -> P (S n) -> P (S (S n))) ->
forall n, P n.
Proof.
now intros P0 P1 IH n; enough (H : P n /\ P (S n)); [|induction n]; intuition.
Qed.
nat_ind2 can be used as follows:
Theorem fraction_addition n m :
even n -> even m ->
Nat.div2 n + Nat.div2 m = Nat.div2 (n + m).
Proof.
induction n using nat_ind2.
(* here goes the rest of the proof *)
Qed.

You can also prove your theorem without induction if you are ok with using the standard library.
If you use Even m in your hypothesis (which says exists n, m = 2*m) then you can use simple algebraic rewrites with lemmas from the standard library.
Require Import PeanoNat.
Import Nat.
Goal forall n m, Even n -> Even m -> n / 2 + m / 2 = (n+m)/2.
inversion 1; inversion 1.
subst.
rewrite <- mul_add_distr_l.
rewrite ?(mul_comm 2).
rewrite ?div_mul; auto.
Qed.
The question mark just means "rewrite as many (zero or more) times as possible".
inversion 1 does inversion on the first inductive hypothesis in the goal, in this case first Even n and then Even m. It gives us n = 2 * x and m = 2 * x0 in the context, which we then substitute.
Also note even_spec: forall n : nat, even n = true <-> Even n, so you can use even if you prefer that, just rewrite with even_spec first...

Related

Coq: help to formalize an informal proof

Theorem ev_ev__ev_full : forall n m,
even (n+m) <-> (even n <-> even m).
Proof.
intros n m. split.
- intros H. split.
+ intros H1. apply (ev_ev__ev n m H H1).
+ intros H1. rewrite plus_comm in H. apply (ev_ev__ev m n H H1).
- intros H.
Output:
n, m : nat
H : even n <-> even m
============================
even (n + m)
Now n can be either even or not even.
if n is even, m is also even. Then by ev_sum theorem (n+m) is also even.
if n is not even, it has the form (n' + 1), where n' is even. m is also not even, and has the form (m' + 1), where m' is even. So their sum is equal to:
n + m = n' + 1 + m' + 1 => n + m = (n' + m') + 2.
even ((n' + m') + 2). After apply ev_SS we get even (n' + m'). As we know that n' is even and m' is even, we apply ev_sum. And this proves the theorem.
How to write this informal proof in coq?
Start with these lemmas:
Theorem even_S (n : nat) : (~even n <-> even (S n)) /\ (even n <-> ~even (S n)). Admitted.
Theorem contra {A B : Prop} (prf : A -> B) : ~B -> ~A. Admitted.
even_S is proven with induction, and I think it's one of the examples of theorems where making the conclusion stronger than you might expect makes it easier to prove (dropping either side of the /\ makes the remaining side difficult). contra is a tautology.
Knowing even_S, the decidability of even n follows straightforwardly from induction on n.
Theorem even_dec (n : nat) : {even n} + {~even n}. Admitted.
This is a decision procedure: even_dec n tells you whether n is even or not, depending on whether it returns the left or right alternative. { _ } + { _ } is the notation for sumbool. It's basically like a bool (it's in Set and so can be destructed in computationally relevant contexts) except it also witnesses one of the two given Props depending on the alternative. In your proof, the first step is branching on this property:
destruct (even_dec n) as [prf_n | prf_n].
If even n, the proof is trivial.
+ admit.
Otherwise, the contrapositive of the backwards implication tells us ~even m. We can also eliminate the nots:
+ pose proof (contra (proj2 H) prf_n) as prf_m.
apply even_S in prf_n.
apply even_S in prf_m.
The rest of the proof (asserting that n = S n', m = S m', even n', even m' and thus even (n + m)) follows with some work (with inversion).
admit.
(I have filled in the admits myself and this path does successfully lead to the proof, but just spilling all the answers is no fun :).)

How to show injectivity of a function?

Here's what I'm trying to prove: Theorem add_n_injective : forall n m p, n + m = n + p -> m = p.
The + is notation for plus, defined as in https://softwarefoundations.cis.upenn.edu/lf-current/Basics.html:
Fixpoint plus (n : nat) (m : nat) : nat :=
match n with
| O ⇒ m
| S n' ⇒ S (plus n' m)
end.
In Agda, one can do cong (n + _) to use the fact that n + m = n + p for any n m p.
Coq's built-in tactices injection and congruence both seemed promising, but they only work for constructors.
I tried the following strategy and kept hitting weird errors or getting stuck:
make an inductive type for bundling up a proof of (n + m = s): Sum (n m s)
use the congruence tactic in a lemma that shows Sum (n m s) = Sum (n p s)
use constructing Sums, destruct, and the lemma to show that n + m = n + p
Is there an easier way to prove this? I feel like there must be some built-in tactic I'm missing or some trickery with unfold.
UPDATE
Got it:
Theorem add_n_injective : forall n m p, n + m = n + p -> m = p.
Proof.
intros. induction n.
- exact H.
- apply IHn. (* goal: n + m = n + p *)
simpl in H. (* H: S (n + m) = S (n + p) *)
congruence.
Qed.
Thanks #ejgallego
Injectivity of plus is not an "elementary" statement, given that the plus function could be arbitrary (and non-injective)
I'd say the standard proof does require induction on the left argument, indeed using this method the proof quickly follows.
You will need injection when you arrive to a goal of the form S (n + m) = S (n + p) to derive the inner equality.

IndProp: ev_plus_plus

(** **** Exercise: 3 stars, standard, optional (ev_plus_plus)
This exercise just requires applying existing lemmas. No
induction or even case analysis is needed, though some of the
rewriting may be tedious. *)
Theorem ev_plus_plus : forall n m p,
even (n+m) -> even (n+p) -> even (m+p).
Proof.
intros n m p H1 H2.
Here is what I got:
1 subgoal (ID 89)
n, m, p : nat
H1 : even (n + m)
H2 : even (n + p)
============================
even (m + p)
I have proven the previous theorem:
Theorem ev_ev__ev : forall n m,
even (n+m) -> even n -> even m.
And wanted to apply it to H1, but
apply ev_ev__ev in H1.
gives an error:
Error: Unable to find an instance for the variable m.
Why can't it find "m" in the expression even (n + m)? How to fix?
Update
apply ev_ev__ev with (m:=m) in H1.
gives a very strange result:
2 subgoals (ID 90)
n, m, p : nat
H1 : even m
H2 : even (n + p)
============================
even (m + p)
subgoal 2 (ID 92) is:
even (n + m + m)
I thought that it will transform H1 to 2 hypothesis:
H11 : even n
H12 : even m
But instead it gave 2 subgoals, the second that we need to prove is more complicated than the initial one:
even (n + m + m)
What's happening here?
The statement forall n m, even (n+m) -> even n -> even m. does not mean "if we have that (n + m) is even then we have both that n is even and that m is even" (this is false, consider n = m = 1). Instead it means "if we have that (n+m) is even, and we have that n is even, then we have that m is even".
There is no way to get H11 : even n and H12 : even m just from H1 : even (n + m) without assuming a contradiction. I would suggest figuring out how to prove your theorem with pen and paper before trying to prove it in Coq.
Because Coq can't figure out what value it should give for m. You can apply the tactic eapply ev_ev__ev in H1. and see the goals
n, m, p : nat
H2 : even (n + p)
H1 : even ?m
============================
even (m + p)
subgoal 2 (ID 17) is:
even (n + m + ?m)
Coq has instantiated the m with a meta variable ?m, and you need to give a witness for this meta variable in the end to finish the proof.
Second approach is just apply the tactic with instantiating the value of m apply ev_ev__ev with (m := m) in H1.
You can see more on apply with tactics in software-foundations https://softwarefoundations.cis.upenn.edu/lf-current/Tactics.html
The thing that is happening is that Coq unifies H1 with the even n argument of ev_ev__ev instead of the even (n+m).
You can tell Coq exactly where you want H1 to go, and use _ wildcards for the places where you let Coq work out the details.
You probably wanted this the term ev_ev__ev n m H1 with type even n -> even m but your apply produced the term ev_ev__ev (n+m) m _ H1 which also left you with some more stuff to prove. To take a look at the proof context, do
Check ev_ev__ev (n+m) m _ H1.

Preserving structure with inductions on 2 variables

I've been learning about Coq's tactics and familiarizing myself with the system by reproving basic facts about natural numbers.
I've been trying to avoid using the theorems that are already proven in the library, and reproving things like the associativity of multiplication, etc.
However, I've been stymied in a couple of cases, where I have a property for n m:nat that I want to prove, but when I try to do induction on both n and m, the structure of the inductive hypothesises is useless for trying to prove the property.
I proved n = m -> o * n = o * m very easily:
Theorem times_alg_left : forall n m o:nat, n = m -> o * n = o * m.
intros n m o H.
rewrite H; reflexivity.
Defined.
But trying to prove S o * n = S o * m -> n = m completely flumoxed me. I decided, after considerable struggles, to try to prove 2 * n = 2 * m -> n = m, but that was no easier.
I end up with situations like this:
Theorem m2_eq : forall n m:nat, 2 * n = 2 * m -> n = m.
intros n m H.
induction n.
destruct m.
reflexivity.
discriminate.
induction m.
discriminate.
1 subgoal
n, m : nat
H : 2 * S n = 2 * S m
IHn : 2 * n = 2 * S m -> n = S m
IHm : 2 * S n = 2 * m -> (2 * n = 2 * m -> n = m) -> S n = m
______________________________________(1/1)
S n = S m
I've got 2 * S n = 2 * S m, but my inductive premises are talking about 2 * n = 2 * S m and 2 * S n = 2 * m.
I can't make anything happen from this situation.
Similarly, I started trying to proof things about Nat.sub and less than or equal to get around this limitation, but I ran into the same situation.
Theorem sub0_imp_le : forall n m:nat, n - m = 0 -> n <= m.
intros n m H.
induction n; induction m.
apply le_n.
apply le_0.
rewrite sub0 in H.
discriminate.
1 subgoal
n, m : nat
H : S n - S m = 0
IHn : n - S m = 0 -> n <= S m
IHm : S n - m = 0 -> (n - m = 0 -> n <= m) -> S n <= m
______________________________________(1/1)
S n <= S m
But I'm in the same pickle where my inductive premises are worthless.
How do I structure my tactics to solve these type of theorems, with 2 nat variables, and some kind of equality or subtraction situation going on?
You need to do induct on one number while generalizing the other, using the generalize dependent tactic, for instance. This is explained in detail in the Software Foundations book.
Using the Software Foundations book Arthur mentioned, I found the exmaple in question. I need to not introduce m before doing induction on n. I needed to do induction on n first instead, then introduce m.
https://softwarefoundations.cis.upenn.edu/lf-current/Tactics.html#lab143
Theorem times_alg_rem_left : forall n o m:nat, (S o) * n = (S o) * m -> n = m.
intros n o.
induction n.
simpl.
intros m eq.
destruct m.
reflexivity.
rewrite (timesz o) in eq.
simpl in eq.
discriminate.
intros m eq.
destruct m.
rewrite (timesz (S o)) in eq.
inversion eq.
apply f_equal.
apply IHn.
rewrite (times_nSm (S o) n) in eq.
rewrite (times_nSm (S o) m) in eq.
apply plus_alg_rem_right in eq.
assumption.
Defined.

Coq - proving something which has already been defined?

Taking the very straightforward proof of "the sum of two naturals is odd if one of them is even and the other odd":
Require Import Arith.
Require Import Coq.omega.Omega.
Definition even (n: nat) := exists k, n = 2 * k.
Definition odd (n: nat) := exists k, n = 2 * k + 1.
Lemma sum_odd_even : forall n m, odd (n + m) -> odd n /\ even m \/ even n /\ odd m.
Proof.
intros n. intros m. left.
destruct H. firstorder.
The state at the end of this block of code is:
2 subgoals
n, m, x : nat
H : n + m = 2 * x + 1
______________________________________(1/2)
odd n
______________________________________(2/2)
even m
To my understanding, it is telling me that I need to prove to it that I have an odd number n and an even number m through the hypothesis? Even though I have already stated than n is odd and m is even? How do I proceed from here?
UPDATE:
After a bit of fidgeting around (in light of the comments), I guess I would have to do something like this?
Lemma even_or_odd: forall (n: nat), even n \/ odd n.
Proof.
induction n as [|n IHn].
(* Base Case *)
left. unfold even. exists 0. firstorder.
(* step case *)
destruct IHn as [IHeven | IHodd].
right. unfold even in IHeven. destruct IHeven as [k Heq].
unfold odd. exists k. firstorder.
left. unfold odd in IHodd. destruct IHodd as [k Heq].
unfold even. exists (k + 1). firstorder.
Qed.
Which means that now:
Lemma sum_odd : forall n m, odd (n + m) -> odd n /\ even m \/ even n /\ odd m.
Proof.
intros n. intros m. left. destruct H. firstorder.
pose proof (even_or_odd n). pose proof (even_or_odd m).
Result:
2 subgoals
n, m, x : nat
H : n + m = 2 * x + 1
H0 : even n \/ odd n
H1 : even m \/ odd m
______________________________________(1/2)
odd n
______________________________________(2/2)
even m
Intuitively, all that I have done is saying that every number is either even or odd. Now I have to tell coq that my odd and even numbers are indeed odd and even (I guess?).
UPDATE 2:
As an aside, the problem is solvable with just firstorder:
Lemma sum_odd : forall n m, odd (n + m) -> odd n /\ even m \/ even n /\ odd m.
Proof.
intros n. intros m. firstorder.
pose proof (even_or_odd n). pose proof (even_or_odd m).
destruct H0 as [Even_n | Odd_n]. destruct H1 as [Even_m | Odd_m].
exfalso. firstorder.
right. auto.
destruct H1. left. auto.
exfalso. firstorder.
Qed.
Your use of left is still incorrect and keeps you from completing the proof. You apply it to the following goal:
odd (n + m) -> odd n /\ even m \/ even n /\ odd m
and it gives:
H : odd (n + m)
______________________________________(1/1)
odd n /\ even m
You are committing to proving that if n + m is odd, then n is odd and m is even. But this is not true: n might be odd and m might be even. Only apply left or right once you have enough information in the context to be sure which one you want to prove.
So let's restart without left:
Lemma sum_odd : forall n m, odd (n + m) -> odd n /\ even m \/ even n /\ odd m.
Proof.
intros n. intros m. firstorder.
pose proof (even_or_odd n). pose proof (even_or_odd m).
At this point we are at:
H : n + m = 2 * x + 1
H0 : even n \/ odd n
H1 : even m \/ odd m
______________________________________(1/1)
odd n /\ even m \/ even n /\ odd m
Now you want to prove something from disjunctions. In order to prove something of the form A \/ B -> C in Coq's constructive logic, you must prove both A -> C and B -> C. You do this by case analysis on the A \/ B (using destruct or other tactics). In this case we have two disjunctions to decompose:
destruct H0 as [Even_n | Odd_n], H1 as [Even_m | Odd_m].
This gives four cases. I'll show you the first two, the last two are symmetric.
Fist case:
H : n + m = 2 * x + 1
Even_n : even n
Even_m : even m
______________________________________(1/1)
odd n /\ even m \/ even n /\ odd m
The assumptions are contradictory: If both n and m are even, then H cannot hold. We can prove this as follows:
- exfalso. destruct Even_n, Even_m. omega.
(Step through this to understand what happens!) The exfalso is not really necessary, but it's good documentation that we are doing a proof by showing that the assumptions contradict.
Second case:
H : n + m = 2 * x + 1
Even_n : even n
Odd_m : odd m
______________________________________(1/1)
odd n /\ even m \/ even n /\ odd m
Now, knowing assumptions that apply in this case, we can commit to the right disjunct. This is why your left kept you from making progress!
- right.
All that remains to be proved is:
Even_n : even n
Odd_m : odd m
______________________________________(1/1)
even n /\ odd m
And auto can handle this.